2015
DOI: 10.1093/gerona/glv038
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Alcohol Consumption and Risk of Dementia Over 43 Years of Follow-Up: A Population-Based Study From the Swedish Twin Registry

Abstract: Averaging more than 12 grams of alcohol per day may increase risk of dementia. Alcohol from spirits appears particularly important for the increased dementia risk. Genetic and/or familial factors do not explain these associations. Alcohol use reduction may be a useful population-wide intervention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
4
38
2
2
Order By: Relevance
“…In a study based on the Swedish Twin Registry with 43 years of follow-up, where dementia was assessed through electronic health records, a quadratic association was found whereby both no alcohol consumption and high alcohol consumption were associated with an increased risk of dementia, although the excess risk in abstainers did not reach statistical significance and the excess risk of high consumption began at 12 g/day (corresponding to around 10.5 units/week). 37 The study also found, as in our investigation, a reduced risk of dementia for moderate wine consumption and a linear increased risk of dementia in those consuming spirits. Furthermore, a recent study based on a nationwide dataset of patients admitted to hospital in France between 2008 and 2013 reported that those with a hospital admission record for alcohol use disorders had a 3.3-times higher risk of dementia in multivariate analysis, 12 providing further support for our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In a study based on the Swedish Twin Registry with 43 years of follow-up, where dementia was assessed through electronic health records, a quadratic association was found whereby both no alcohol consumption and high alcohol consumption were associated with an increased risk of dementia, although the excess risk in abstainers did not reach statistical significance and the excess risk of high consumption began at 12 g/day (corresponding to around 10.5 units/week). 37 The study also found, as in our investigation, a reduced risk of dementia for moderate wine consumption and a linear increased risk of dementia in those consuming spirits. Furthermore, a recent study based on a nationwide dataset of patients admitted to hospital in France between 2008 and 2013 reported that those with a hospital admission record for alcohol use disorders had a 3.3-times higher risk of dementia in multivariate analysis, 12 providing further support for our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Several other previous studies have suggested that heavy alcohol consumption could increase the risk of cognitive impairment and dementia, in contrast to the present findings. This might be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…This might indicate that moderate lifestyles, in general, which can vary across cultural environments, could protect against cognitive deterioration. 20 Several other previous studies have suggested that heavy alcohol consumption could increase the risk of cognitive impairment and dementia, 21,22 in contrast to the present findings. This might be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…The Swedish Twin Registry study, with 12,326 participants, showed that each additional gram of alcohol over 1.16 g per day from wine was associated with a 2% decreased risk of dementia, yet the highest amount of alcohol intake from wine was associated with an increased dementia risk by 1% [ 66 ]. A cross-sectional study, used high-resolution structural MRI on 589 multi-ethnic community-dwelling elderly to assess the effect of alcohol intake and on imaging markers of brain structure.…”
Section: Resultsmentioning
confidence: 99%